Wi-Fi Bat–Echolocating a Device Connected to a Wi-Fi Transmitter Using Wi-Fi Signals - Horngacher, Alexander; Larsson , Jacob; Lu, David; Remmelgas, Noah; Valfridsson, Emil (My University, 2025)
This thesis presents the design of a Wi-Fi sensing system that is capable of estimating the distance between two devices using Wi-Fi signals. The system leverages channel state information (CSI) extracted from a network interface controller (NIC) as well as the received signal strength indicator (RSSI). In this system, a Raspberry Pi equipped with a compatible NIC served as the receiver and a transmitter which transmitted Wi-Fi packets at varying distances. The thesis also discusses the limitations of such a system as signal noise and environmental multipath effects, and reflects on the ethical implications of Wi-Fi-based sensing with regard to privacy.